Role of emissions and meteorology in the recent PM2.5 changes in China and South Korea from 2015 to 2018 - Bae, Minah; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Jhoon; Kim, Soontae (Environmental Pollution, 2021)
The PM2.5 reduction in China, dominantly due to emissions, was faster than in South Korea. Emission reductions in an upwind area do not guarantee corresponding air quality improvement in the downwind. In this study, we examined the change rates of PM2.5 concentrations, aerosol optical depth (AOD), and the concentrations of PM2.5 precursors, such as SO2 and NO2, in China and South Korea using surface and satellite observations from 2015 to 2018. To quantify the impacts of the emissions and meteorology on the concentration changes, we performed a series of air quality simulations with year-specific meteorology and a fixed anthropogenic emissions inventory. The surface PM2.5 observations in China and South Korea decreased at rates of 9.1 and 4.3%/yr during the study period, respectively. The AODs from Moderate Resolution Imaging Spectroradiometer (MODIS) and Geostationary Ocean Color Imager (GOCI) also decreased faster over China than the AODs over South Korea. For the PM2.5 decrease in China, the emission impact was more significant (73%) than the meteorology impact (27%). On the contrary, in South Korea, the emissions and meteorology impacts on PM2.5 reductions were similar (51% vs 49%). The SO2 concentration over China in 2018 significantly reduced to approximately half of the level in 2015. In turn, the sulfate concentration in Baengnyeong (BN), located in a downwind pathway from China to South Korea, decreased at a rate of 0.79%/month. However, the nitrate concentration in BN showed an increasing trend due to the non-linear chemical reactions among sulfate-nitrate-ammonium. The increased nitrate compensated for the reduced PM2.5 concentration from the sulfate decrease at BN. Additionally, the number of high (>50 μg/m3) PM2.5 concentration days continuously decreased in China, but the number in South Korea increased. It is noted that emission reductions in an upwind area do not guarantee corresponding air quality improvement in the downwind area when complex secondary aerosol formation processes, as well as spatiotemporal changes in meteorology, are involved in the transboundary transport of air pollutants.
Keywords: Aerosol optical depths; Air quality improvement; Air quality simulation; Anthropogenic emissions; Moderate resolution imaging spectroradiometer; Satellite observations; Spatio-temporal changes; Sulfate concentrations; Air Pollutants; Air Pollution; China; Environmental Monitoring; Meteorology; Particulate Matter; Republic of Korea; Emissions; Meteorology; PM2.5; Satellite observation; Surface observation